THE EFFECT OF USING DEEPL ON THE WRITING SKILLS OF 11TH GRADE STUDENTS IN HOSPITALITY MAJOR AT SMK NEGERI 1 SINGARAJA - Purnamawati, Luh Desi; Santosa, Made Hery; Dewi, Kadek Sintya (Universitas Suryakancana, 2025)
This research aims to determine the effect of using DeepL on EFL students' writing skills. An explanatory sequential mixed-methods design with quasi experimental and open-ended interviews was used in this research. Through purposive sampling, seventy-one EFL students from North Bali, Indonesia participated in the quasi-experimental phase, with ten additional students volunteering for interview sessions. The writing test data were analyzed using descriptive and inferential analysis, while the interview transcripts were subjected to Interactive Model analysis. The research results show that there is a medium effect (0.52) of using DeepL on EFL students' writing skills. The interactive model analysis revealed students' positive responses to DeepL features such as autocorrect and alternative word suggestions, which facilitated improved grammatical accuracy, an enjoyable learning experience, increased language proficiency, and increased self-confidence. However, there are challenges such as connectivity issues and unfamiliarity with the application that hinder its effectiveness. In conclusion, DeepL shows potential as a transformative tool in language acquisition and writing instruction, although there are certain obstacles that need to be overcome in order to achieve optimal effectiveness.